Performance degradation and analysis of 10-cell anode-supported SOFC stack with external manifold structure. (15th April 2017) - Yan, Dong; Liang, Lingjiang; Yang, Jiajun; Zhang, Tao; Pu, Jian; Chi, Bo; Li, Jian
Abstract: This study describes the development of solid oxide fuel cell (SOFC) stack with external manifold structure. The stack used anode supported cells with size of 11 cm × 11 cm which are fabricated by tape casting, screen-printing and co-sintering. Computer simulation was employed to evaluate the gas distribution in the external manifold stack. The 10-cell stack was operated at 750 °C with hydrogen as fuel and air as oxidant and generated output power of 360 W, corresponding to power density of 440 mW/cm 2 . The degradation performance was investigated for over 750 h under the current density of 370 mA/cm 2 . Posttest analysis of the SOFC stack was operated to investigate the factors related to the performance degradation such as microstructure of electrodes, sealing, contact resistance and oxidation of metal interconnect. The study presented here showed the stack with external manifold can be considered as a strong candidate for SOFC stack design. Highlights: A 10-cell external manifold SOFC stack was build and discharged for over 750 h. The relationship between leaking and degradation has been discovered. Reasons of degradation has been identified and quantified.